2023
DOI: 10.1101/2023.03.15.532802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NAC1 directs CEP1-CEP3 peptidase expression and modulates root hair growth in Arabidopsis

Abstract: Plant genomes encode a unique group of papain-type Cysteine EndoPeptidases (CysEPs) containing a KDEL endoplasmic reticulum (ER) retention signal (KDEL-CysEPs or CEPs). CEPs process the cell-wall scaffolding EXTENSIN proteins (EXTs), which regulate de novo cell wall formation and cell expansion. Since CEPs are able to cleave EXTs and EXT-related proteins, acting as cell wall-weakening agents, they may play a role in cell elongation. Arabidopsis thaliana genome encodes three CEPs (AtCPE1-AtCEP3). Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…These findings suggest that these cysteine proteases are involved in developmental cell elongation and cell separation processes dependent on cell wall remodeling. In agreement, it was demonstrated that CEPs process the extensin proteins, which control cell wall structure and cell expansion [188].…”
Section: What Can Callus-expressed Genes Teach Us?mentioning
confidence: 55%
“…These findings suggest that these cysteine proteases are involved in developmental cell elongation and cell separation processes dependent on cell wall remodeling. In agreement, it was demonstrated that CEPs process the extensin proteins, which control cell wall structure and cell expansion [188].…”
Section: What Can Callus-expressed Genes Teach Us?mentioning
confidence: 55%